2014
DOI: 10.1007/s10072-014-1754-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the acupoints PC 6 Neiguan and LR 3 Taichong on cerebral blood flow in normal subjects and in migraine patients

Abstract: Acupuncture has been proven to be effective in the treatment of various cardiovascular disorders; it acts both on the peripheral flow and on the cerebral flow. Our study aimed to evaluate the effects of the insertion of PC 6 Neiguan and LR 3 Taichong acupoints on the cerebral blood flow (CBF) in the middle cerebral artery (MCA). These effects were measured in a group of patients suffering from migraine without aura (Group M) and in a healthy control group (Group C). In the study, we included 16 patients suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…2009). Neuroimaging studies have shown that acupuncture stimulation on this acupoint can modulate a wide range of cortical and limbic brain region activity (Chang et al, 2009;Quirico et al, 2014;Yoo et al, 2004;. Constant-current electrical impulses produced from a battery-driven TEAS apparatus (NDK, Osaka, Japan) were delivered on bilateral acupoints via two adhesive electrode pads placed on the acupoint skin (Fig.…”
Section: Of 29mentioning
confidence: 99%
“…2009). Neuroimaging studies have shown that acupuncture stimulation on this acupoint can modulate a wide range of cortical and limbic brain region activity (Chang et al, 2009;Quirico et al, 2014;Yoo et al, 2004;. Constant-current electrical impulses produced from a battery-driven TEAS apparatus (NDK, Osaka, Japan) were delivered on bilateral acupoints via two adhesive electrode pads placed on the acupoint skin (Fig.…”
Section: Of 29mentioning
confidence: 99%
“…2,5 The lack of specificity in migraine diagnosis arises, in part, because diagnostic markers related to neurobiological mechanisms are lacking. 15 Hemodynamic changes during migraine, indexed by alterations in regional cerebral blood flow (CBF), have been described using both non-invasive 5,[15][16][17] and invasive [18][19][20][21][22][23] imaging techniques, such as PET. 7,8 In analogy, the gate control theory of pain, 9,10 focused on chronic pain, postulated that neural gates in the spinal cord can be opened (or closed) by signals descending from the brain, as well as by sensory information ascending from the body.…”
Section: Introductionmentioning
confidence: 99%
“…Nei‐Guan (PC6) is also one of the most commonly used point for TEAS treatment of psychiatric disorders . Neuroimaging has shown that acupuncture stimulation on this acupoint can modulate a wide range of cortical and limbic brain region activity . Constant‐current electrical impulses produced from a battery‐driven TEAS apparatus (Shenzhen Ryan Medical Device, Shenzhen, China; model code, SNH‐138; power supply, DC9V(006P); product standard code, YZB/Guangdong 0138–2003) were delivered on bilateral acupoints via two adhesive electrode pads placed on the acupoint skin.…”
Section: Methodsmentioning
confidence: 99%